Takhrij and Syarah Hadith of Agrotechnology Study of Black Seed Content in Increasing Body Resistance During the Covid-19 Pandemic - Lisma Sabilah; Wahyudin Darmalaksana; Safarinda Nurdianawati (Gunung Djati Conference Series, 2021)
This study aims to discuss the hadith of the Prophet. about Black Seed. This research method is a qualitative type through literature and field studies with the takhrij and sharah hadith approaches. The results and discussion of this study are takhrij and syarah traditions about Black Seed which are known to have immunostimulant activity, and contain fatty acids and various nutrients that are beneficial to the body. The conclusion of this research is that Black Seed according to takhrij and sharah hadith with an agrotechnological approach is a traditional medicine that has been used to cure all kinds of diseases.